2016
DOI: 10.1007/s00382-016-3308-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing mid-latitude dynamics in extreme event attribution systems

Abstract: tracks are too zonal over the Atlantic in the CMIP5 and AMIP5 ensembles, but better simulated in HadAM3P with the exception of being too weak over Western Europe. In all cases, the CMIP5 and AMIP5 performances were almost identical, suggesting that the biases in atmospheric modes considered here are not strongly coupled to SSTs, and perhaps other model characteristics such as resolution are more important. For event attribution studies, it is recommended that rather than taking statistics over the entire CMIP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…It is well-documented that climate models reasonably well capture changes in global patterns of surface temperature, which are primarily thermodynamically controlled. In contrast, there is much less confidence in circulation aspects of climate change, which are primarily controlled by dynamics343536. We assume here that even models that don’t correctly simulate certain details of planetary wave dynamics responses37— an issue we will examine later– are still likely to get the QRA fingerprint right, allowing us to draw reliable real-world conclusions about how climate change may impact the phenomenon of QRA.…”
mentioning
confidence: 99%
“…It is well-documented that climate models reasonably well capture changes in global patterns of surface temperature, which are primarily thermodynamically controlled. In contrast, there is much less confidence in circulation aspects of climate change, which are primarily controlled by dynamics343536. We assume here that even models that don’t correctly simulate certain details of planetary wave dynamics responses37— an issue we will examine later– are still likely to get the QRA fingerprint right, allowing us to draw reliable real-world conclusions about how climate change may impact the phenomenon of QRA.…”
mentioning
confidence: 99%
“…More recently, the prominent role of air‐sea coupling associated with the Gulf and Kuroshio currents (e.g., Häkkinen et al, ; O‘Reilly & Czaja, ; O‘Reilly et al, ) and the El Niño–Southern Oscillation in modulating block intensities and preferred locations over the North Pacific (NP; Barriopedro et al, ; Barriopedro & Calvo, ) has been demonstrated. The role of interactions with the ocean is of interest given that recent analyses of coupled general circulation models (GCMs) show an underrepresentation of blocking frequency, especially over the Atlantic (Masato et al, ; Mitchell et al, ; Vial & Osborn, ), although there are variations in these biases depending on whether Pacific versus Euro‐Atlantic blocking sectors are considered (Matsueda et al, ) and the level of horizontal resolution (see, for example, D’Andrea et al, ; Davini & D‘Andrea, ; Schiemann et al, ; Vial & Osborn, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, given the importance of both dynamic and thermodynamic effects (2,3,9,25,43), we demonstrate the potential to systematically evaluate the occurrence of physical "ingredients" that contribute to individual events.…”
mentioning
confidence: 99%